Hacking exposed wireless : wireless security secrets & solutions - Cache, Johnny; Liu, Vincent; Wright, Joshua (Hacking exposed, 2010)
"Build and configure your Wi-Fi attack arsenal with the best hardware and software tools; explore common weaknesses in WPA2 networks through the eyes of an attacker; leverage post-compromise remote client attacks on Windows 7 and Mac OS X; master attack tools to exploit wireless systms, including Aircrack-ng, coWPAtty, Pyrit, IPPON, FreeRADIUS-WPE, KillerBee, and Wireshark; evaluate your threat to software update impersonation attacks on public networks; assess your threat to eavesdropping attacks ... using commercial and custom tools; develop advanced skills leveraging Software Defined Radio and other flexible frameworks; apply comprehensive defenses to protect your wireless devices and infrastructure." -- Cover, p. [4]